Cutaneous T-cell pseudolymphoma in a 3-year old girl - Roszkiewicz, Jadwiga; Lange, Magdalena; Cegielska, Agnieszka (Dermatology Review/Przegląd Dermatologiczny, 2009)
Introduction. Cutaneous pseudolymphomas (CPL) constitute a hete-rogeneous group of skin disorders, defined as benign lymphocytic infiltration of the skin. Although pseudolymphomas can mimic B-cell and T-cell lymphomas, their character is benign with a tendency to spontaneous remission. In a majority of cases CPL is idiopathic. However, sometimes it can be provoked by arthropods\' bites, infections (herpes zoster, Borrelia burgdorferi), tattoos, acupuncture, trauma, vaccinations, desensitization or medications. Objective. To present a case of coexistence of severe combined immunodeficiency with disseminated T-cell pseudolymphoma cutis. Case report. A 3-year old patient with numerous disseminated nodular skin lesions localized on the face as well as lower and upper extremities was treated in our department. The lesions appeared during the summer, did not cause any symptoms and were resistant to local therapy with corticosteroids. On the basis of histopathological examination of the skin biopsy, which revealed dense infiltrates of histiocytes and T-cells, the diagnosis of T-cell pseudolymphoma was established. Due to severe, recurrent infections of the respiratory tract and chronic diarrhoea the patient was consulted in the Children’s Memorial Health Institute, where after many diagnostic procedures severe combined immunodeficiency syndrome was recognized. Conclusions. We present a case of a 3-year old girl with severe combined immunodeficiency, who developed disseminated cutaneous T-cell pseudolymphomatous reaction due to insect bites and who achieved complete remission after hematopoietic stem cell transplantation.